The Effectiveness of Scientific Approach Based Guided Discovery Learning Model to Improve Student Learning Outcomes (Journal of Primary Education, 2020)
The purpose of this study was to improve student learning outcomes in mathematics about the circumference and area of flat shapes in class IV SDN Magersari with the Guided Discovery Learning model (GDL) based on Scientific Approach (SA). Type of this research is classroom action research or penelitian tindakan kelas (PTK) with 2 cycles action in this study. Data collection technique was used observation, test, and documentation. The research compared the SA-based GDL learning model to the learning outcomes of fourth grade mathematics with the number of students, namely 25. For indicators of achieving student success, 75% was classical. The results of cycle 1, there were 18 students who completed with a percentage of 72%, but in cycle 1 students still had difficulty doing the final test. Then the results of cycle 2, there were 21 students who completed with a percentage of 84% of the results of the evaluation of cycle 1 in the final test of cycle 2 students mastered the material more. There was an increase of 12% from cycle 1 to cycle 2, which means that the research succeeded in exceeding the classical completeness indicator. Based on the analysis, can be concluded the SA-based GDL model can improve the student learning outcomes in the mathematics subject at fourth grade student.